Emerging trends in watershed management - Yadav, R. P. (Delhi : Satish Serial Pub. House, 2010)
Papers presented at a Conference on "Environmental and Livelihood Security through Resource Management in Northern India, held at Chandigarh during 29-31 October 2007.
Keywords: Watershed management; Watershed management; Natural resources; Water harvesting; Sustainable development